Human occupations in the mountains of central Tierra del Fuego: an archaeological appoach - Mansur, Maria Estela; de Angelis, Hernan Horacio; Parmigiani, Vanesa Esther
The aim of this paper is to inform about the results of archaeological investigations carried out up to now in the central strip of Isla Grande de Tierra del Fuego, the main island of the fuegian archipelago. The central sector of the island is a mountainous and woody environment, characterized by development of sub Antarctic forest as well as by its various environments and microenvironments with different resources. The investigation search to evaluate the interrelationship between environment, resources and population dynamics in this area, that we consider as a key to understand the dynamics of mobility throughout the island. It is organized around hypothesis regarding differential resources supply in the various environments of the area, and the possible circulation of hunter-gatherers, as well as the role of both factors in the variability of the archaeological record. Fil: Mansur, Maria Estela. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: de Angelis, Hernan Horacio. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Parmigiani, Vanesa Esther. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina